2019
DOI: 10.5709/acp-0272-4
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation During Conceptual Processing of Action and Sound Verbs

Abstract: embodied cognition grounded cognition theory action-related concepts sound-related concepts language functional magnetic resonance imaging Grounded cognition approaches to conceptual representations postulate a close link between conceptual knowledge and the sensorimotor brain systems. The present fMRI study tested, whether a feature-specific representation of concepts, as previously demonstrated for nouns, can also be found for action-and sound-related verbs. Participants were presented with action-and soundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 107 publications
3
8
0
Order By: Relevance
“…This assumption is based on the fact that in most works in this area, the compatibility effect was studied using the example of the problem of assigning an object to one category or another (Tucker and Ellis, 2001et al, 2007, Bub et al, 2013. The results of the studies mentioned in the theoretical review are generally consistent with studies that used the fMRI method : upon presentation of images or words, activation of motor zones was observed if the given stimulus was an object with which action was possible (for example, a hammer); significant activation occurred upon presentation of stimuli denoting movement (verbs) (Popp, et al, 2019). It can be said that the task of assigning an object to one category or another is closer to the experimental conditions of studies using fMRI than the task presented in this study.…”
Section: Discussionsupporting
confidence: 63%
“…This assumption is based on the fact that in most works in this area, the compatibility effect was studied using the example of the problem of assigning an object to one category or another (Tucker and Ellis, 2001et al, 2007, Bub et al, 2013. The results of the studies mentioned in the theoretical review are generally consistent with studies that used the fMRI method : upon presentation of images or words, activation of motor zones was observed if the given stimulus was an object with which action was possible (for example, a hammer); significant activation occurred upon presentation of stimuli denoting movement (verbs) (Popp, et al, 2019). It can be said that the task of assigning an object to one category or another is closer to the experimental conditions of studies using fMRI than the task presented in this study.…”
Section: Discussionsupporting
confidence: 63%
“…Importantly, the ACE is an embodied effect that primarily indicates the functional role of the motor system in language comprehension and concept processing (Klepp et al, 2019;Morey et al, 2021). Using such an appropriate index to detect motor representations of abstract concepts, our results provide behavioral evidence for modality-specific representations (representations within modality-specific systems for perception, action, and emotion) of motor features of abstract verbs, similar to neuroimaging studies on concrete words (e.g., Hauk et al, 2004;Popp et al, 2019;Kuhnke et al, 2020). Thus, the degree of involvement of the motor system in the processing of abstract words may vary according to their dominant features of the abstract word.…”
Section: Motor Features Of Abstract Verbs Causally Affect Their Repre...supporting
confidence: 69%
“…Thus, the degree of involvement of the motor system in the processing of abstract words may vary according to their dominant features of the abstract word. Recent studies have shown that conceptual processing involves both modality-specific sensorimotor areas and higher-level multimodal regions ( Fernandino et al, 2016 ; Popp et al, 2019 ; Harpaintner et al, 2020 ; Kuhnke et al, 2020 ). Further research is required to provide neural evidence of the causal links between the dominant features in abstract concepts and their representations in modality-specific and multimodal regions.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, this hierarchical system is flexible, with different regions being recruited dynamically depending on the task ( Hoenig et al. 2008 ; Kemmerer 2015 ; Popp et al. 2019b ).…”
Section: Introductionmentioning
confidence: 99%